Interpretation of structural imbalances in the Iraqi economy According to the three-gap model of duration (2003 - 2017) - Owish, Hussein Ali (International Journal of Psychosocial Rehabilitation, 2020)
The Iraqi economy has many economic components and capabilities that contribute effectively to raising economic growth rates and improving the standard of living and social life in Iraq, but it suffers from many changes and imbalances that have been negatively reflected directly or indirectly on the performance of the economy in general , accompanied by many Factors, accumulations and impulses that burdened its budget and worked on slowing its growth, disrupting its economic and structural structure, and failing to achieve its development goals. Among these factors are Iraq’s entry into many foreign wars such as the eight-year war with Iran, the invasion of Kuwait, imposing international sanctions, internal conflicts and opposition to the regime, such as the Northern War in the Kurdistan region In the era of the seventies and the local revolution in the early nineties of the last century, and the adoption of many policies and procedures in order to avoid these crises, they led to a great dependence on the oil rentier revenues, the only source in the structure of exports and the marginalization of the rest of the sectors, the fact that Iraq ranks third in the world in its oil reserves and the main resource in preparing public budgets, as well as the emergence of economic and social phenomena that have undermined development and a deficiency in growth such as unemployment poverty and corruption to enter Iraq in the development syndrome, namely the three gaps that has become a major constraint on investment and economic development represented by the internal divide - a gap of savings & investment weakness in his savings and turn them into anus fruits , external gap - a gap of import and export - as a result of failure and disruption of structural in apparatus production and low efficiency for the lack of competitiveness and cover the needs of the local market, and the gap of the budget - a gap of income and expenditure - addressed by researchers independently from the previous two gaps and represented the absorptive capacity gap that responds to variable investment and no other variables other to exist closely between the need for investment to domestic savings Which is characterized by insufficient coverage of investments and its response to my stock The foreign exchange mechanism, which has become deficient to meet and nourish the investment structure required by development, thus the two gaps became associated with the third gap, so that the shortage of savings and the insufficiency of commodity exports, except for oil, are combined with the decline in the outcome of public revenues to lead to the imbalance of the economic structure and the delinquency of the economy to rentierism clearly and this is what we will review in the body of the research.